Lung abscess in a professional rugby player: an illustration of overtraining syndrome?. Issue 10 (4th May 2007) - Castinel, Bernard H; Adam, Philippe; Prat, Christophe; Mourlanette, Pierre
Abstract : As in other endurance sports, the intensity of training sessions and the pace of competition has significantly increased since rugby union became a professional sport. The case history is presented of a professional rugby player who was diagnosed with septicaemia and a lung abscess following an infected wound to the ear. The symptoms only resolved after a large dose of antibiotics and 3 months of rest. It is hypothesised that this may be an example of overtraining syndrome, but complementary blood analyses would be necessary to confirm this. The case underlines the importance of clinically assessing the individual capacity of players to recover, in order to prevent overtraining and to maintain a high level of performance during the whole season.